Modified supraauricular approach in recurrent preauricular sinus: A case report - Hafiz, Al; Julianda, Wahyu (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
The preauricular sinus (PAS) also known as the fossa fistula sac or depression is located near the external auricle at the posterior end of the stalk of the ascending helix. Most cases of PAS are asymptomatic and do not require treatment. Surgery is performed if there are signs of infection or recurrence. Incomplete PAS resection is the most common cause of recurrence. The real problem with surgical resection of PAS is the high recurrence rate after sinusectomy. We report the case of a 22-year-old woman who complained of a mass in her left ear that was enlarging for the past 3 months. The patient had previously undergone two operations at the same site but they were recurrent. Physical examination revealed a non-hyperemic painful cystic mass. A few days after the operation the patient recovered and the pain in front of his left ear disappeared. The patient can close his eyes and lift his forehead symmetrically and show no signs of infection. A follow-up examination 1-2 weeks after surgery in the Department of Ear Nose Throat Head and Neck Surgery (ENT-HNS) showed that the general condition of the patient was good and there were no signs of infection. After 6 months the patients ears returned to normal and there was no recurrence 6 months after surgery. There is a scar along the leading edge of the helix. The patient was diagnosed with a recurrent PAS complicated by a preauricular cyst and treated with sinusectomy using a modified supraauricular approach and resection of the preauricular cyst. Sinusectomy with a modified supraauricular approach is an effective technique and is superior to simple sinusectomy due to its low recurrence rate with minimal complications and superior aesthetic appearance. This modified supraauricular approach achieved excellent functional and aesthetic results in this patient.